2014
DOI: 10.5539/ibr.v7n3p115
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Competitive Strategies, Environmental Factors and Human Resources Architecture Relations

Abstract: There is a widespread notion that organizational strategies are the dominant factors in the creation of human resources (HR) management policies in enterprises. This study examines the relation between an organization's strategies, corporate HR policies and operating performance. At the end of the research, it was observed that (1) The high rate of change of the environment orientates establishments towards a more participative management perception, towards empowerment and flexibility. (2) While innovative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Daya saing juga merupakan kemampuan untuk menandingi atau bahkan mengalahkan perusahaan terbaik dunia dalam hal biaya dan kualitas barang atau jasa (Omerzel & Gulev, 2011). Sumber daya perusahaan penting dalam mendukung strategi dan meningkatkan kinerja bisnis termasuk dari sisi pelayanan, hal ini ditunjukkan oleh Chumaidiyah (2014); Dogan et al, (2014); Ocak & Findik (2019); Omerzel & Gulev (2011); Pasaribu et al, (2016). Berdasarkan beberapa hasil penelitian, dirumuskan hipotesis 1 bahwa sumber daya berpengaruh signifikan terhadap aspek pelayanan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Daya saing juga merupakan kemampuan untuk menandingi atau bahkan mengalahkan perusahaan terbaik dunia dalam hal biaya dan kualitas barang atau jasa (Omerzel & Gulev, 2011). Sumber daya perusahaan penting dalam mendukung strategi dan meningkatkan kinerja bisnis termasuk dari sisi pelayanan, hal ini ditunjukkan oleh Chumaidiyah (2014); Dogan et al, (2014); Ocak & Findik (2019); Omerzel & Gulev (2011); Pasaribu et al, (2016). Berdasarkan beberapa hasil penelitian, dirumuskan hipotesis 1 bahwa sumber daya berpengaruh signifikan terhadap aspek pelayanan.…”
Section: Pendahuluanunclassified
“…Efisiensi produksi dan efisiensi distribusi yang telah dilakukan PDAM Kabupaten Jember akan meningkatkan aspek teknis pelayanan dan pertumbuhan konsumen karena dari sisi internal dan eksternal mereka merasa sumber daya yang dimilikinya telah dikelola dengan baik. Hasil penelitian sesuai dengan hasil penelitian Chumaidiyah (2014); Dogan et al (2014); Omerzel & Gulev (2011); Pasaribu et al, (2016).…”
Section: Pendahuluanunclassified
“…Based on their f indings, Qazvin's climate should be considered having a relatively warm and dry climate with cold winters in which the avoidance of cold in winter has been given more priority than the heat in summer. Dogan (2014) tested the relationship between organisation strategies, the policies of human integrated resources and the operation of work. It was observed that the high rate of changing environment led installations towards a more participative management understanding, empowerment, active choice, and employment policies.…”
Section: Cultural and Regional Identitymentioning
confidence: 99%